Telefonoaudiologia no tratamento do transtorno fonológico no Sistema Único de Saúde: ensaio clínico pragmático - Silveira, Jesus Cláudio Gabana da (2024)
Purpose: To compare face-to-face speech therapy treatment with telepractice and hybrid therapy for children with speech sound disorder/phonological impairment (PI) in the Unified Health System (SUS), using a therapeutic approach of complexity in light of the IMFC; to examine the therapeutic approaches for PI most frequently published in the leading Brazilian SLP journals over the past 10 years; to assess the effectiveness of the treatment methods used in the research, with numerical data; to characterize the socio-economic and race/ethnicity profiles of the participants; and to present the pathways followed by children with PI in telepractice, in-person, and hybrid therapy through the IMFC. Method: A pragmatic clinical trial was conducted in an outpatient Speech Therapy Service in SUS, with 12 male participants, with a mean age of 6:2, a speech-language diagnosis of PI, hearing thresholds within normal limits, and the ability to perform basic orofacial praxis. Participants were divided into three therapeutic groups: G1) telepractice; G2) face-to-face; G3) hybrid: face-to-face with telepractice activities. Therapy was conducted using the complexity approach ABAB-Withdrawal and multiple probes, over 11 sessions, adapted to one session per week of treatment. Participants were assessed before and after the therapeutic cycle using the Phonology section of the ABFW. Based on the evaluation results, two articles were developed. One article presented quantitative data from the PCC-R, levels of PI, the number of fully and partially acquired phonemes, and qualitative data on the intention to treat. The improvement of participants was associated with the intention to treat and socioeconomic and race/color data. The other article presented the therapeutic pathways followed within the IMFC in the sample. A therapeutic cycle of 11 sessions was analyzed. Results: The overall mean (n = 12) of the PCC-R and the number of acquired phonemes increased significantly (p≤0.05%) after the therapeutic cycle. There was an association between improvement and acquisition of the target sound; and between improvement and intention to treat. No association was found between improvement and race/color or sociodemographic profile. Nine participants followed new pathways within the IMFC, and three participants did not acquire new phonemes. The target sound of the therapy was fully or partially acquired by seven participants. Two participants did not acquire the target sound but followed new pathways within the IMFC. Conclusion: All three therapeutic groups studied showed similar results, with 75% of participants improving, considering target sound acquisition, increased PCC-R, and the number of acquired phonemes. New pathways within the IMFC occurred, even among participants who did not acquire the treated target sound. These results suggest that it is feasible to implement telepractice within SUS.